Jingle All the Way - Levant, Brian; Lloyd, Jake, 1989-; Martin Mull; Phil Hartman; Rita Wilson; Robert Conrad; Sinbad; Arnold Schwarzenegger (USA 1492 Pictures, 1996)
Harried mattress salesman Howard Langston is late for his son Jamie's karate class. To placate his unhappy son he asks him if there is anything he wants for Christmas. He wants Turbo Man. Howard naturally forgets to get it, and being Christmas eve no stores have it in stock. So Howard embarks on a comical quest to find one.
A harried father decides to dream the impossible dream, to get that year's hot toy for his son just before Christmas Day.
Randy Kornfield
Languages: English, French Subtitles: English, Spanish
Keywords: Adventure; Comedy; Family; Action